Experimental and analytical investigations into the seismic behavior and resistance of corroded reinforced concrete walls. (1st July 2021) - Zhou, Yan; Zheng, Shansuo; Chen, Liuzhuo; Long, Li; Dong, Liguo; Zheng, Jie
Highlights: Accelerated corrosion tests conducted on RC structural wall specimens. Experimental investigations on seismic behavior of corroded RC structural walls. A modified model was proposed and verified to obtain seismic responses of corroded walls. Prediction equations for lateral load resistance of corroded walls were derived. Abstract: Chloride attacks will deteriorate the physical and mechanical properties of materials and finally degrade the seismic performance of reinforced concrete (RC) structural walls. At present, there are difficulties in evaluating the seismic resistance of RC structures with walls in offshore environments due to insufficient research on the cross-fields of material corrosion and seismic performance of corroded structural walls. In this paper, accelerated corrosion tests and quasi-static cyclic loading tests were conducted on seven RC structural walls to investigate their performance under the combined influencing parameters of corrosion level, aspect ratio, axial force, and reinforcement ratio. Afterward, a modified model was proposed and verified to obtain predictions about seismic responses of corroded structural walls based on experimental data. Finally, prediction equations for lateral load resistance of corroded structural walls with different aspect ratios were derived from parametric investigation through the proposed modeling method. The comparative analysis demonstrates that the proposed model and equations produced good predictions and could be adopted to evaluate the residual seismic performance of corroded RC structural walls.